Identification of Small Molecule Inhibitors of the Deubiquitinating Activity of the SARS-CoV-2 Papain-Like Protease: in silico Molecular Docking Studies and in vitro Enzymatic Activity Assay - Pitsillou, Eleni; Liang, Julia; Ververis, Katherine; Lim, Kah Wai; Hung, Andrew; Karagiannis, Tom C. (Frontiers in Chemistry, 2020)
COVID-19 is an ongoing pandemic caused by the SARS-CoV-2 virus with important political, socio-economic, and public health consequences. Inhibiting replication represents an important antiviral approach, and in this context two viral proteases, the SARS-CoV-2 main and papain-like proteases (PLpro), which cleave pp1a and pp1ab polypeptides, are critical. Along with protease activity, the PLpro possesses deubiquitinating activity, which is important in immune regulation. Naphthalene-based inhibitors, such as the well-investigated GRL-0617 compound, have been shown to possess dual effects, inhibiting both protease and deubiquitinating activity of the PLpro. Rather than binding to the canonical catalytic triad, these type of noncovalent inhibitors target an adjacent pocket, the naphthalene-inhibitor binding site. Using a high-throughput screen, we have previously identified the dietary hypericin, rutin, and cyanidin-3-O-glucoside compounds as potential protease inhibitors targeting the naphthalene-inhibitor binding site. Here, our aim was to investigate the binding characteristics of these compounds to the PLpro, and to evaluate deubiquitinating activity, by analysing seven different PLpro crystal structures. Molecular docking highlighted the relatively high affinity of GRL-0617 and dietary compounds. In contrast binding of the small molecules was abolished in the presence of ubiquitin in the palm subdomain of the PLpro. Further, docking the small molecules in the naphthalene-inhibitor binding site, followed by protein-protein docking revealed displacement of ubiquitin in a conformation inconsistent with functional activity. Finally, the deubiquitinating activity was validated in vitro using an enzymatic activity assay. The findings indicated that the dietary compounds inhibited deubiquitinase activity in the micromolar range with an order of activity of GRL-0167, hypericin >> rutin, cyanidin-3-O-glucoside > epigallocatechin gallate, epicatechin gallate, and cefotaxime. Our findings are in accordance with mechanisms and potential antiviral effects of the naphthalene-based, GRL-0617 inhibitor, which is currently progressing in preclinical trials. Further, our findings indicate that in particular hypericin, rutin, and cyanidin-3-O-glucoside, represent suitable candidates for subsequent evaluation as PLpro inhibitors.